Ordering Properties of the First Eigenvector of Certain Similarity Matrices - Matthijs J. Warrens; Alexandra de Raadt (Journal of Mathematics)
It is shown for coefficient matrices of Russell-Rao coefficients and two asymmetric Dice coefficients that ordinal information on a latent variable model can be obtained from the eigenvector corresponding to the largest eigenvalue.